2002
DOI: 10.1097/00000539-200207000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Does Spinal Anesthesia Cause Hearing Loss in the Obstetric Population?

Abstract: Sixty obstetric patients were enrolled in the study to examine the possible effects of spinal anesthesia on their hearing. By using an audiometer, the patient's hearing was evaluated before delivery, after delivery, and for the following 2 days. There was no significant change of hearing in any of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 8 publications
3
22
0
3
Order By: Relevance
“…The magnitude of change in hearing threshold was statistically significant but small (Tables 2 and 4), as with earlier studies documenting postspinal hearing loss [9,10,16]. Intravascular volume replacement affects post-spinal hearing loss [11].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The magnitude of change in hearing threshold was statistically significant but small (Tables 2 and 4), as with earlier studies documenting postspinal hearing loss [9,10,16]. Intravascular volume replacement affects post-spinal hearing loss [11].…”
Section: Discussionsupporting
confidence: 82%
“…If the postoperative dB level was significantly higher than the preoperative value, it signified a change in hearing ability [9]. In Group S, there was a significant increase in the postoperative mean hearing threshold at 500 Hz (right ear) as compared with the preoperative hearing threshold ( Table 2; P b 0.05).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…They suggested that the explanation of the hearing loss could be a biological mechanism similar to endolymphatic hydrops, resulting from perilymphatic hypotension due to ''loss of liquor during and after the spinal anaesthesia''. However, Finegold et al [9] tested the hypothesis that women undergoing elective caesarean delivery with a subarachnoid block (SAB) suggesting that they may experience hearing loss due to lumbar puncture and cerebrospinal fluid leakage causing hypoacusis. They could find no difference in the hearing levels in the period immediately before and 2 days after the caesarean.…”
Section: Discussionmentioning
confidence: 99%